Częstość urodzeń i stan rozwoju noworodków przedwcześnie urodzonych z masą ciała poniżej 2500 g w rejonie Gdańska - Orkwiszewska, Anna; Gładykowska-Rzeczycka, Judyta Julia (Polskie Towarzystwo Antropologiczne, 1994)
THE FREQUENCY OF BIRTH AND MORPHOLOGY OF PREMATURE NEWBORN IN THE GDANSK DISTRICT. In the years 1977 to 1987 the number of premature babies bom in the Gdansk district decreased by 1.5% as well as the number of the newborns with weight less than 2,500 g.
THE FREQUENCY OF BIRTH AND MORPHOLOGY OF PREMATURE NEWBORN IN THE GDANSK DISTRICT